REPRESENTATIONS OF TRAUMA IN AFRICAN MIGRANT FICTION (2021)
African migrant fiction, which recreates characters’ experiences at home and abroad, is increasingly preoccupied with the representation of dystopian realities. Critical appraisals of the fiction have largely focused on the representation of varied mobilities – migration, exile, transnationalism and afropolitanism – without adequate attention to the depiction of migrant characters’ experiences of traumatic stress, despite its ample representation in the fiction. This study was, therefore, designed to examine the recreation of trauma and characters’ responses to traumatic stress in selected African migrant fiction with a view to establishing that traumatic experiences are not limited to characters’ natal homes. Homi Bhabha’s model of the Postcolonial Theory and Cathy Caruth’s and Judith Herman’s models of Trauma Theory, served as the framework. The interpretative design was used. Ali Farah’s Little Mother (LM), Laila Lalami’s Hope and Other Dangerous Pursuits (HODP), Ben Jelloun’s Leaving Tangier (LT), Chika Unigwe’s On Black Sisters’ Street (OBSS), Alain Mabanckou’s Blue White Red (BWR), Brian Chikwava’s Harare North (HN), Fatou Diome’s The Belly of the Atlantic (TBA), and Noviolet Bulawayo’s We Need New Names (WNNN) were purposively selected for their depiction of loss, trauma and suffering. The novels were subjected to critical analysis. Trauma in the novels is doubled-edged, aligning with the dominant estimation of trauma as a double wound. Traumatogenic contexts and events in the postcolony as well as in the diaspora dominate the novels. Pre-migration stressors such as unemployment, poverty and sexual assault characterise the postcolony in LT, OBSS, HODP and TBA; while displacement, deprivation and violence abound in WNNN, HN, LM and BWR, all leading to characters’ experience of Continuous Traumatic Stress. Characters’ response to pre-migration stressors in all the novels is flight. Repetitively traumatised by oppressive poverty, displacement and the inconsistencies that define life in the postcolony, the characters fled their fatherland for the West through legitimate and illegitimate routes. In the diaspora, post-migration stressors are activated by characters’ experiences of disillusionment, racism, joblessness, physical and mental assaults, unhomeliness, the trauma of a paperless existence and the perpetual fear of police brutality. Characters’ responses to post-migration stressors range from developing Post-Traumatic Stress Disorder (PTSD) to committing suicide. Azel in LT and the nameless protagonist in HN experience dissolution of self and suffer from PTSD. In WNNN and LM, Tshaka Zulu, Uncle Kojo and Axad suffer from mental illnesses, while Moussa in TBA commits suicide. However, characters like Massala-Massala in BWR, Aunt Fostalina and Darling in WNNN, Faten in HODP and Efe, Ama and Joyce in OBSS largely display resilience in the face of trauma. There is recurring adoption of multiple narrative voices, symbolism and journey motif in OBSS, LM, HODP and HN, while irony and traumatic realism are employed in LT, WNNN, TBA and BWR. Migrant characters’ precarious, liminal and subaltern existence, both at home and abroad, bears witness to trauma’s mobility across space and time in African migrant fiction. This destabilises the hegemonic conception of the West as the Promised Land.